Ingi, a 5.2-Kb dispersed sequence element from Trypanosoma brucei that carries half of a smaller mobile element at either end and has homology with mammalian lines - Kimmel, B.E.; Ole-MoiYoi, O.K.; Young, J.R. (Informa UK Limited, 1987)
A dispersed repetitive element named ingi, which is present in the genome of the protozoan parasite Trypanosoma brucei, is described. One complete 5.2-kilobase element and the ends of two others were sequenced. There were no direct or inverted terminal repeats. Rather, the ends consisted of two halves of a previously described 512-base-pair transposable element (G. Hasan, M.J. Turner, and J.S. Cordingley, Cell 37:333-341, 1984). Oligo(dA) tails and possible insertion site duplications suggested that ingi is a retroposon. The sequenced element appears to be a pseudogene copy of an original retroposon with one or more open reading frames occupying most of its length. Significant homologies of the encoded amino acid sequences with reverse transcriptases and mammalian long interpersed nuclear element sequences suggest a remote evolutionary origin for this kind of retroposon.